Theme-Antics and the The-Eerie Class: CrWit(t)icism in wRap - David Walton (Miscelánea: A Journal of English and American Studies)
Rather than an abstract, I shall offer an abstruct or obstract: something which could be said to stand in the way rather than lighten it. Yet, I would have it retain something of the abstract—an incorporeal substance (a hal[l]o) floating above what lies below. What is it that lies below? Any attempt to describe what happens there in a language which gestures towards an unambiguous style, clarity of argument, neat concision etc. would militate against my tendency to de-scribe. I would say that this is not so much an article but an "art-tickle." Here, then, a ludic cycle, pedagogical joy-ride into the uncommon, unorthodox terror-tory of liteRAREry theory, via vary-us forms of song (rap, punk, blues): an attempt to Sir-jest (with a modicrumb of wit) an alter-native means of intro-juicing concepts. But at a cost. This is to be done in a lang-wage (O mischievous sprite!) that imp-lies, through its very shApe, the condition of the linguistic sign (post Derrida, Lacan, Kristeva & C”), witch may be useful in itself, as a kind of exemplum to the way theory may be presented or written about. So, I offer a few comments on motorvation. And to finish, there are "A Few RidDling Quest-ions for the feary glass" and a "Vermiform Appendix" of other possibilities.